A Case Study of Academics’ Knowledge Sharing Motivations at Malaysian Public Academic Institutions - Saad, Alsaleh (Journal of Education and Vocational Research, 2013)
This qualitative case study aims to explore and describe the academicians’ knowledge sharing motivations in a Malaysian public university. A single case study was conducted with the aim to gather deeper insights on the knowledge sharing motivation. Data were collected through semi-structured interviews. A total of 15 renowned academicians were interviewed. Content analysis method was used to extract the knowledge sharing motivations from the qualitative data. The research results reveal seven important factors which motivate academicians to share their knowledge. These motivations are build reputation, acknowledgement (includes gain rewards, get a promotion, and recognition), to be knowledgeable, reciprocity, vision and mission, mentoring, personal beliefs (includes culture, sense of responsibility, and religion). The research comprehensive analysis and results would expand an area of knowledge sharing motivations among academicians in universities which may still theoretically and empirically not adequately explored and described.